Understanding digital literacies a practical introduction - Jones, Rodney H. 1959-; Hafner, Christoph A. (Routledge, Taylor & Francis Group, 2021)
"Understanding Digital Literacies Second Edition provides an accessible and timely introduction to new media literacies. This book equips students with the theoretical and analytical tools with which to explore the linguistic dimensions and social impact of a range of digital literacy practices. Each chapter in the volume covers a different topic, presenting an overview of the major concepts, issues, problems, and debates surrounding it, while also encouraging students to reflect on and critically evaluate their own language and communication practices. Features of the second edition include: • expanded coverage of a diverse range of digital media practices that now includes Instagram, Snapchat, TikTok, Tinder, and WhatsApp; • two entirely new chapters on mobility and materiality, and surveillance and privacy; • updated activities in each chapter which engage students in reflecting on and analysing their own media use; • e-resources featuring a glossary of key terms and supplementary material for each chapter, including additional activities and links to useful websites, articles, and videos. This book is an essential textbook for undergraduate and postgraduate students studying courses in new media and digital literacies."
Literaturverzeichnis Seiten 277-293
Keywords: Neue Medien; Medienkompetenz; Informationskompetenz; Digitalisierung; Englischunterricht; Internet